The graduates’ employability skills : a case study at Langkawi Development Authority (LADA) / Hanani Abdullah and Siti Najihah Abd Rahim - Abdullah, Hanani; Abd Rahim, Siti Najihah (2019)
This study examines the skills that preferred by the top management and middle management that will impact the graduates employability status. This is because the skills are prerequisite for the managers and employees success, especially for newly graduate students. This study is to evaluate the employability skills of the graduates that preferred by the top management and middle management in LADA and to assess how employability skills are perceived by potential employers. Three sets of employability skills have been used in this study such as entrepreneurship skills, digital literacy, and project management skills. A questionnaire has been developed which included above dimensions and was distributed among top management and middle management in LADA. The respondents’ opinions were assessed using a Likert scale analysis that shows divergent opinions from strongly agrees to strongly disagree. This study was conducted to find out that the selected skills are the skills that most preferred by the employers. Therefore, it will help the graduates to prepare themselves to fulfill the requirement by the employer to promote their employability status.